2012
DOI: 10.1007/s00332-012-9139-0
|View full text |Cite
|
Sign up to set email alerts
|

Rise and Fall of Periodic Patterns for a Generalized Klausmeier–Gray–Scott Model

Abstract: Rise and fall of periodic patterns in a generalized Klausmeier-Gray-Scott model van der Stelt, S. Link to publicationCitation for published version (APA): van der Stelt, S. (2012). Rise and fall of periodic patterns in a generalized Klausmeier-Gray-Scott model. Amsterdam. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(143 citation statements)
references
References 81 publications
2
141
0
Order By: Relevance
“…Supercriticality has been proven in an asymptotic scaling of (1) in one space dimension, 60 and numerically, it is found that this holds in a broad range of parameter space. Through Theorem 2, for advection c > 0, the Turing-Hopf bifurcation is a natural mechanism for the formation of striped or banded vegetation patterns.…”
Section: -7mentioning
confidence: 87%
See 3 more Smart Citations
“…Supercriticality has been proven in an asymptotic scaling of (1) in one space dimension, 60 and numerically, it is found that this holds in a broad range of parameter space. Through Theorem 2, for advection c > 0, the Turing-Hopf bifurcation is a natural mechanism for the formation of striped or banded vegetation patterns.…”
Section: -7mentioning
confidence: 87%
“…In Figure 3, we plot the values of a T for 2c ¼ 0, 182.5, 365, 500, and 1000, together with a square root function since a T grows as ffiffi ffi c p for large c, in a certain scaling regime. 60 Now that we understand the influence of both parameters a and m, we can also fix c and infer the dependence a T ¼ a T (m) for free. The following approximation complementary to (25) can be made:…”
Section: -mentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we presented a picture of pattern formation and collapse that occurs via two Turing bifurcations, but finite-wavelength Turing instability is not the only mechanism for vegetation collapse observed in models. In a study of the generalized Klausmeier model by van der Stelt et al [20], a patterned vegetated state collapses directly to desert via long-wavelength, sideband, and Hopf instabilities. Additionally, homoclinic snaking [21,22] has been proposed as a mechanism for the stabilization and motion of localized patterned states that emerge en route to desertification [23].…”
Section: Pattern Transitions In the Model By Von Hardenberg Et Almentioning
confidence: 99%